Wacana Sosial dalam Penggunaan Siger Lampung: Antara Pelestarian Tradisi dan Adaptasi Budaya - Evita Listi Maharani; Salma Safinatunnajah; Vivas Dwi Toti Divaldo; Purwanto Putra; Zaimasuri Zaimasuri; Ahmad Riza Faizal (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article discusses the social phenomenon related to using Siger Lampung as one of the cultural attributes typical of the Lampung region. Currently, the use of Siger Lampung is increasingly varied, ranging from clothing, decoration, and public facilities to commercial places. Siger, which is currently more often used in the context of architecture and design, requires adjustments that some traditional and cultural figures may not approve of. This adjustment also requires a careful approach to ensure that the essence of its culture is not lost and can continue to survive. Given these obstacles and challenges, the community and government need to work together on the importance of maintaining Siger as an integral part of Lampung culture. Through support through education, promotion, and cultural initiatives, Siger can remain a symbol of recognition in this modern era. This study aims to analyze the role of Siger Lampung in preserving traditions and cultural adaptation in a multi-ethnic society. By understanding the dynamics of Siger use, this cultural symbol is expected to function as a uniform tool and collective identity in various communities.